Impact of a 4-Week Intensified Endurance Training Intervention on Markers of Relative Energy Deficiency in Sport (RED-S) and Performance Among Well-Trained Male Cyclists - Stenqvist, Thomas Birkedal; Torstveit, Monica Klungland; Faber, Jens; Melin, Anna Katarina (Frontiers in Endocrinology, 2020)
Cyclists often apply block periodization to high training volumes in meso- and macrocycles to optimize training adaptation and to prepare for competition. Body mass influences performance in many sports, including endurance disciplines, and conditions related to the syndrome Relative Energy Deficiency in Sports (RED-S) such as metabolic adaptations and premature osteoporosis have also been reported in male cyclists. This study aimed to determine how a 4-week mesocycle of intensified endurance training designed to increase performance, would affect markers of RED-S in well-trained male cyclists. Twenty-two participants (age: 33.5 ± 6.6 years, height: 181.4 ± 5.2 cm, weight: 76.5 ± 7.4 kg, peak oxygen uptake (VO2peak): 63.5 ± 6.6 mL·kg−1·min−1) were recruited and instructed to maintain their background training load and to follow a supervised training protocol consisting of three high-intensity interval training sessions per week with a work duration of 32 min per session. Protocols included pre- and postintervention assessment of resting metabolic rate (RMR) using a ventilated hood, body composition and bone health by dual-energy X-ray absorptiometry (DXA), blood samples, energy intake, and aerobic performance. The interval training increased participants' aerobic performance—peak power output [4.8%, p < 0.001], VO2peak [2.4%, p = 0.005], and functional threshold power [6.5%, p < 0.001] as well as total testosterone levels [8.1%, p = 0.011]—while no changes were observed in free testosterone [4.1%, p = 0.326]. Bodyweight, body composition, and energy intake were unchanged from pre- to post-test. Triiodothyronine (T3) [4.8%, p = 0.008], absolute RMR [3.0%, p = 0.010], relative RMR [2.6%, p = 0.013], and RMRratio [3.3%, p = 0.011] decreased, and cortisol levels increased [12.9%, p = 0.021], while no change were observed in the total testosterone:cortisol ratio [1.6%, p = 0.789] or the free testosterone:cortisol (fT:cor) ratio [3.2%, p = 0.556]. A subgroup analysis of the five participants with the largest increase in fT:cor ratio, revealed a greater improvement in functional threshold power (9.5 vs. 2.5%, p = 0.037), and higher relative RMR (0.6 vs. −4.2% p = 0.039, respectively). In conclusion, 4 weeks of intensified endurance interval training increased the athletes' aerobic performance and testosterone levels. However, negative changes in markers related to RED-S, such as a reduction in RMR and T3, and an increase in cortisol were observed. These results indicate the complexity involved, and that male athletes are at risk of developing clinical indications of RED-S even during a short 4-week endurance training mesocycle.